1983 Survey of Doctoral Programs in Accounting in the United States and Canada - Crum, William F.; Garner, Don E. (The Accounting Review, 1985)
[This paper reports the results of a sixth triennial canvass covering 74 doctoral programs in the United States. For the first time, six Canadian doctoral programs are included. Data are provided on universities offering doctoral degrees, degrees awarded between 1980 and 1982, candidates in coursework stage, and candidates in dissertation stage. Canadian statistics, presented in a separate section, indicate a small but growing number of candidates and graduates. Doctoral degrees granted in the three-year period by United States universities increased in each year, reaching an all-time high of 177 in 1982. Offsetting this is a forecasted decrease in graduates for 1983 and 1984. Enrollments of candidates at the dissertation stage declined by 6.4 percent since the 1980 survey. Candidates at the coursework stage declined by 4.4 percent. The national three-year doctoral output has remained in the range of 424 to 469 since 1971.]